A note on Fibonacci matrices of even degree. (1st November 2001) - Elia, Michele
Abstract : This paper presents a construction ofm -by-m irreducible Fibonacci matrices for any evenm . The proposed technique relies on matrix representations of algebraic number fields which are an extension of the golden section field. The explicit construction of some6 -by-6 and8 -by-8 irreducible Fibonacci matrices is given.